Thermal modeling and analysis of double-sided water-cooled permanent magnet linear synchronous machines. Issue 2 (7th March 2016) - Chen, Yi; Yao, Yihua; Lu, Qinfen; Huang, Xiaoyan; Ye, Yunyue
Abstract : Purpose: – With the popularization of permanent magnet linear synchronous machines (PMLSMs) in recent years, the temperature rise has attracted increasingly attention since excessive heat generated in the windings could deteriorate the electromagnetic performance. In order to solve this problem, adopting water-cooled system is an effective method. The purpose of this paper is to investigate a 12-slot/11-pole (12S/11P) water-cooled double-sided PMLSM, which adopts the all teeth wound concentrated winding and shifted armature ends. Design/methodology/approach: – Based on 2D finite element analysis (FEA), the thermal performances, such as temperature distribution, the optimization of water flow rate and the influence of demagnetization, are investigated under the condition of continuous duty. Then the maximum current density and average thrust force are calculated for PMLSMs with or without water-cooled system. Finally, the detailed comparison is made between single-sided PMLSM and double-sided PMLSM. Findings: – With water-cooled system, the thermal performance of PMLSM can be improved, such as an efficient decrease of temperature rise, restriction of permanent magnet demagnetization and a dramatic increase of the maximum thrust force. It is found that the water flow rate has a significant impact on temperature rise, which can be optimized according to demands. Originality/value: – Electromagnetic and thermal coupled analysis is proposed in this paper. It can approximately predict thermal performance and save the manual iteration time at the same time. This method also can provide as a reference of thermal analysis for other PMLSMs.